Flexible inorganic multilayer ferroelectric film and preparation method thereof

The flexible inorganic multi-layer ferroelectric film prepared through sol-gel process and laser peeling technology, combined with lanthanum nitriate or cobalt ferrate inducing layers, solves the problems of low breakdown field strength and large energy loss of electronic devices, and achieves high Preparation of flexible films of quality, low energy consumption, suitable for wearable electronic devices.

CN119156115APending Publication Date: 2024-12-17HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270574.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Currently, electronic devices are facing the problems of low breakdown field strength, large energy loss, poor sample quality and poor flexibility. Especially in the field of wearable electronic devices, the high-temperature sintering process of traditional piezoelectric ceramic materials is complex and rigid, which limits their application.

Method used

The precursor solution of lead zirconium titanate layer and inducing layer is prepared by sol-gel process, and a flexible inorganic multi-layer ferroelectric film is prepared by spin coating and laser peeling technology, combining lanthanum nitriate or cobalt ferrate as the inducing layer to enhance the film's Breakdown field strength and reduce energy loss.

Benefits of technology

The preparation of flexible inorganic multi-layer ferroelectric film is realized, which significantly improves the breakdown field strength, reduces energy loss, simplifies the process flow, is suitable for large-scale production, and increases the service life of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156115A_ABST
    Figure CN119156115A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible inorganic multilayer ferroelectric film and a preparation method thereof, and belongs to the technical field of flexible piezoelectric nano energy collectors and preparation thereof. The invention aims to solve the problems of low breakdown field strength, large energy loss, poor sample quality and poor flexibility of the current electronic device. The inorganic multilayer ferroelectric film is prepared on the sapphire substrate by adopting a sol-gel method in combination with a spin-coating annealing process, and then the inorganic multilayer ferroelectric film is transferred to the flexible substrate of polyethylene terephthalate by utilizing a laser lift-off process, so that flexible preparation of the inorganic film is realized. The preparation process provided by the invention is simple and convenient in flow, novel in method, environment-friendly and pollution-free in preparation process and suitable for large-scale production. The flexible inorganic multilayer ferroelectric film prepared by the invention can effectively reduce energy loss, improve the breakdown field strength of the film and prolong the service life of an electronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible piezoelectric nano energy collectors and preparation thereof, and specifically relates to a flexible inorganic multilayer ferroelectric film and a preparation method thereof. Background Art

[0002] Flexible piezoelectric nano energy harvesters have become a research hotspot in academia and industry due to their great advantages in powering wearable electronic devices. With the rapid development of portable wearable smart devices and Internet of Things technology, the autonomous power supply technology of miniaturized, low-power wearable electronic devices has attracted extensive research interests at home and abroad. Current electronic devices face shortcomings such as low breakdown field strength, large energy loss, and poor sample quality. Common piezoelectric ceramics require complex high-temperature sintering processes, and their large stiffness limits their application in the field of flexible wearable electronic devices. Making inorganic ferroelectric thin film materials flexible can further apply the performance advantages of these materials to wearable electronic devices, which is an important development direction in the field of next-generation wearable electronic devices. Summary of the invention

[0003] The purpose of the present invention is to solve the problems of low breakdown field strength, large energy loss, poor sample quality and poor flexibility faced by current electronic devices, and to provide a flexible inorganic multilayer ferroelectric film and a preparation method thereof.

[0004] A flexible inorganic multilayer ferroelectric film is composed of lead zirconate titanate layers (Pb 0.52 Zr 0.48 The induction layer is composed of lanthanum nickel oxide (LaNiO3) or cobalt ferrite (CoFe2O4).

[0005] The lead zirconate titanate layer is abbreviated as PZT; the lanthanum nickel oxide is abbreviated as LNO; and the cobalt ferrite is abbreviated as CFO.

[0006] A method for preparing a flexible inorganic multilayer ferroelectric thin film is specifically completed by the following steps:

[0007] 1. Preparation of precursor solution:

[0008] ①, using the sol-gel process to prepare the lead zirconate titanate layer precursor solution;

[0009] The concentration of the lead zirconate titanate layer precursor solution described in step 1① is 0.25 mol / L to 0.4 mol / L;

[0010] ②, using sol-gel process to prepare the induction layer precursor solution;

[0011] When the induction layer described in step 1② is lanthanum nickelate, the concentration of the induction layer precursor solution is 0.05 mol / L to 0.15 mol / L;

[0012] When the induction layer described in step 1② is cobalt ferrite, the concentration of the induction layer precursor solution is 0.15mol / L to 0.25mol / L;

[0013] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate;

[0014] 3. First, the multilayer ferroelectric film and polyethylene terephthalate are irradiated with ultraviolet light for a period of time, then a polyurethane adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for a period of time, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0015] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0016] 5. Magnetron sputtering technology is used to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then a passivation layer is covered on the surface to obtain a flexible inorganic multilayer ferroelectric film.

[0017] Principle of the present invention:

[0018] The present invention uses a sol-gel method to prepare a lead zirconate titanate layer precursor solution and an induction layer precursor solution, and improves the quality of the multilayer film by designing the structure of the lead zirconate titanate layer and the induction layer, significantly improving the breakdown field strength of the multilayer film and reducing the energy loss of the film. At the same time, the new process of laser peeling is used to realize the flexible preparation of the multilayer film, which has certain application prospects in the fields of flexible nano energy collection and the like.

[0019] Beneficial effects of the present invention:

[0020] (1) The flexible multilayer ferroelectric thin film prepared by the annealing process of the present invention has good crystallization;

[0021] (2) After the introduction of lanthanum nickel oxide (LNO) induction layer, the (100) and (200) diffraction peak intensities of the flexible inorganic multilayer ferroelectric film are significantly improved, while after the introduction of cobalt ferrite (CFO) induction layer, the diffraction peak intensity of the flexible inorganic multilayer ferroelectric film does not change significantly;

[0022] (3) The preparation process of the present invention is simple, the method is novel, the preparation process is environmentally friendly and pollution-free, and is suitable for large-scale production;

[0023] (4) The flexible inorganic multilayer ferroelectric film prepared by the present invention can effectively reduce energy loss, increase the breakdown field strength of the film, and increase the service life of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0025] Figure 2 X-ray diffraction comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Comparative Examples 1 to 3;

[0026] Figure 3 Atomic force microscope comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0027] Figure 4 A comparison diagram of hysteresis loops of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0028] Figure 5 Weibull distribution diagram of the breakdown field strength of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4. DETAILED DESCRIPTION

[0029] Specific implementation method 1: In this implementation method, a flexible inorganic multilayer ferroelectric film is composed of a lead zirconate titanate layer and an induction layer; the induction layer is lanthanum nickelate or cobalt ferrite.

[0030] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the thickness of the flexible inorganic multilayer ferroelectric thin film is 0.8 μm to 1.2 μm. The other steps are the same as those of specific implementation method 1.

[0031] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: a method for preparing a flexible inorganic multilayer ferroelectric thin film is specifically completed by the following steps:

[0032] 1. Preparation of precursor solution:

[0033] ①, using the sol-gel process to prepare the lead zirconate titanate layer precursor solution;

[0034] The concentration of the lead zirconate titanate layer precursor solution described in step 1① is 0.25 mol / L to 0.4 mol / L;

[0035] ②, using sol-gel process to prepare the induction layer precursor solution;

[0036] When the induction layer described in step 1② is lanthanum nickelate, the concentration of the induction layer precursor solution is 0.05 mol / L to 0.15 mol / L;

[0037] When the induction layer described in step 1② is cobalt ferrite, the concentration of the induction layer precursor solution is 0.15mol / L to 0.25mol / L;

[0038] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate;

[0039] 3. First, the multilayer ferroelectric film and polyethylene terephthalate are irradiated with ultraviolet light for a period of time, then a polyurethane adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for a period of time, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0040] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0041] Fifth, using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film. The other steps are the same as those in the first or second embodiment.

[0042] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0043] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0044] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0045] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g: 21 mL: 5 mL: 2 mL: 2.7 mL: 1.5 mL. The other steps are the same as those in the first to third embodiments.

[0046] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 1②, the induction layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0047] In step 1②, the induction layer precursor solution is prepared by using a sol-gel process, which is specifically completed in the following steps:

[0048] When the induction layer is lanthanum nickelate, the preparation method of the induction layer precursor solution is as follows: nickel nitrate and lanthanum nitrate are added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and aged in the dark for 24 hours to obtain an induction layer precursor solution;

[0049] The mass volume ratio of the nickel nitrate, lanthanum nitrate, ethylene glycol methyl ether, glacial acetic acid, and acetylacetone is 2g:1g:13mL:2mL:1.8mL;

[0050] When the induction layer is cobalt ferrite, the preparation method of the induction layer precursor solution is as follows: add cobalt nitrate and ammonium ferric sulfate to citric acid, continue stirring until completely dissolved, add 25% by mass concentrated ammonia water dropwise to control the pH to pH=7, and then stir at a constant temperature of 75°C to complete the reaction, stop heating when the solution is a viscous gel, naturally cool to room temperature, and age in the dark for 24 hours to obtain an induction layer precursor solution;

[0051] The mass volume ratio of the cobalt nitrate, ammonium ferric sulfate and citric acid is 1.6 g:1.8 g:15 mL. The other steps are the same as those in the first to fourth embodiments.

[0052] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the annealing temperature in step 2 is 650° C. to 750° C. and the annealing time is 5 min to 10 min. The other steps are the same as those in specific embodiments 1 to 5.

[0053] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the thickness of the polyethylene terephthalate in step 3 is 40 μm to 60 μm; in step 3, the multilayer ferroelectric film and the polyethylene terephthalate are first irradiated with ultraviolet light for 50 min to 70 min; in step 3, the polyethylene terephthalate is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 50 min to 70 min. The other steps are the same as those in specific embodiments 1 to 6.

[0054] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the wavelength of the XeCl excimer laser in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV; the time for irradiating the sapphire substrate with the XeCl excimer laser in step 4 is 5 min to 10 min. The other steps are the same as those in specific embodiments 1 to 7.

[0055] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the interdigital electrodes described in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15nm to 30nm, and the thickness of the Au electrodes is 120nm to 150nm. The other steps are the same as those of specific embodiments 1 to 8.

[0056] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the passivation layer in step 5 is polyurethane or epoxy resin; the finger width of the interdigitated electrode in step 5 is 80 μm to 120 μm, and the finger spacing is 1 mm to 3 mm. The other steps are the same as specific embodiments 1 to 9.

[0057] The following examples are used to verify the beneficial effects of the present invention:

[0058] Embodiment 1: The preparation method of PZT flexible ferroelectric thin film (PZT) is specifically completed according to the following steps:

[0059] 1. Preparation of precursor solution:

[0060] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0061] The concentration of the lead zirconate titanate layer precursor solution described in step 1① is 0.3 mol / L;

[0062] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0063] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0064] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0065] 2. Spin coating the lead zirconate titanate layer precursor solution layer by layer on a double-sided polished sapphire substrate by using a spin coating method, with the number of spin coating layers being 12 layers of PZT, and then performing a rapid annealing treatment to obtain a multilayer ferroelectric thin film on the sapphire substrate;

[0066] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0067] The thickness of each PZT layer in step 2 is 0.08 μm;

[0068] 3. First, the multilayer ferroelectric film and polyethylene terephthalate are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0069] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0070] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0071] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0072] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0073] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a PZT flexible ferroelectric film (PZT);

[0074] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0075] The passivation layer described in step 5 is polyurethane;

[0076] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0077] Example 2: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / LNO / PZT (PZT-LNO-1), which is specifically completed by the following steps:

[0078] 1. Preparation of precursor solution:

[0079] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0080] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0081] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0082] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0083] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0084] ②, using sol-gel process to prepare the induction layer precursor solution;

[0085] The induction layer described in step 1② is lanthanum nickelate (LNO), and the concentration of the induction layer precursor solution is 0.1 mol / L;

[0086] The preparation method of the induction layer precursor solution described in step 1② is as follows: nickel nitrate and lanthanum nitrate are added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and aged in the dark for 24 hours to obtain an induction layer precursor solution;

[0087] The mass volume ratio of the nickel nitrate, lanthanum nitrate, ethylene glycol methyl ether, glacial acetic acid, and acetylacetone is 2g:1g:13mL:2mL:1.8mL;

[0088] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 6 layers of PZT, 6 layers of LNO, and 6 layers of PZT, and then rapid annealing is performed to obtain a multilayer ferroelectric film on the sapphire substrate;

[0089] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0090] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each LNO layer is 0.03 μm;

[0091] 3. First, the multilayer ferroelectric film and polyethylene terephthalate are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0092] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0093] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0094] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0095] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0096] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / LNO / PZT (PZT-LNO-1);

[0097] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0098] The passivation layer described in step 5 is polyurethane;

[0099] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0100] Example 3: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / LNO / PZT / LNO / PZT (PZT-LNO-2), which is specifically completed by the following steps:

[0101] 1. Preparation of precursor solution:

[0102] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0103] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0104] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0105] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0106] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0107] ②, using sol-gel process to prepare the induction layer precursor solution;

[0108] The induction layer described in step 1② is lanthanum nickelate (LNO), and the concentration of the induction layer precursor solution is 0.1 mol / L;

[0109] The preparation method of the induction layer precursor solution described in step 1② is as follows: nickel nitrate and lanthanum nitrate are added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and aged in the dark for 24 hours to obtain an induction layer precursor solution;

[0110] The mass volume ratio of the nickel nitrate, lanthanum nitrate, ethylene glycol methyl ether, glacial acetic acid, and acetylacetone is 2g:1g:13mL:2mL:1.8mL;

[0111] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 4 layers of PZT, 3 layers of LNO, 4 layers of PZT, 3 layers of LNO and 4 layers of PZT, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate;

[0112] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each LNO layer is 0.03 μm;

[0113] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0114] 3. First, the multilayer ferroelectric film and polyethylene terephthalate (PET) are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0115] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0116] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0117] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0118] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0119] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / LNO / PZT / LNO / PZT (PZT-LNO-2);

[0120] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0121] The passivation layer described in step 5 is polyurethane;

[0122] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0123] Example 4: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / LNO / PZT / LNO / PZT / LNO / PZT (PZT-LNO-3), which is specifically completed by the following steps:

[0124] 1. Preparation of precursor solution:

[0125] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0126] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0127] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0128] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0129] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0130] ②, using sol-gel process to prepare the induction layer precursor solution;

[0131] The induction layer described in step 1② is lanthanum nickelate (LNO), and the concentration of the induction layer precursor solution is 0.1 mol / L;

[0132] The preparation method of the induction layer precursor solution described in step 1② is as follows: nickel nitrate and lanthanum nitrate are added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and aged in the dark for 24 hours to obtain an induction layer precursor solution;

[0133] The mass volume ratio of the nickel nitrate, lanthanum nitrate, ethylene glycol methyl ether, glacial acetic acid, and acetylacetone is 2g:1g:13mL:2mL:1.8mL;

[0134] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 3 layers of PZT, 2 layers of LNO, 3 layers of PZT, 2 layers of LNO, 3 layers of PZT, 2 layers of LNO and 3 layers of PZT, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate;

[0135] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each LNO layer is 0.03 μm;

[0136] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0137] 3. First, the multilayer ferroelectric film and polyethylene terephthalate (PET) are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0138] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0139] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0140] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0141] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0142] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / LNO / PZT / LNO / PZT / LNO / PZT (PZT-LNO-3);

[0143] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0144] The passivation layer described in step 5 is polyurethane;

[0145] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0146] Comparative Example 1: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / CFO / PZT (PZT-CFO-1), which is specifically completed by the following steps:

[0147] 1. Preparation of precursor solution:

[0148] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0149] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0150] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0151] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0152] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0153] ②, using sol-gel process to prepare the induction layer precursor solution;

[0154] The induction layer described in step 1② is cobalt ferrite (CFO), and the concentration of the induction layer precursor solution is 0.2 mol / L;

[0155] The preparation method of the induction layer precursor solution described in step 1② is as follows: add cobalt nitrate and ammonium ferric sulfate to citric acid, continue stirring until completely dissolved, add 25% concentrated ammonia water dropwise to control the pH to pH = 7, and then stir at a constant temperature of 75°C to complete the reaction. When the solution is a viscous gel, stop heating, cool naturally to room temperature, and age in the dark for 24 hours to obtain an induction layer precursor solution;

[0156] The mass volume ratio of the cobalt nitrate, ammonium ferric sulfate and citric acid is 1.6g:1.8g:15mL;

[0157] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 6 layers of PZT, 6 layers of CFO, and 6 layers of PZT, and then rapid annealing is performed to obtain a multilayer ferroelectric film on the sapphire substrate;

[0158] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each CFO layer is 0.03 μm;

[0159] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0160] 3. First, the multilayer ferroelectric film and polyethylene terephthalate (PET) are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0161] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0162] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0163] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0164] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0165] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / CFO / PZT (PZT-CFO-1);

[0166] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0167] The passivation layer described in step 5 is polyurethane;

[0168] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0169] Comparative Example 2: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / CFO / PZT (PZT-CFO-2), which is specifically completed by the following steps:

[0170] 1. Preparation of precursor solution:

[0171] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0172] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0173] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0174] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0175] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0176] ②, using sol-gel process to prepare the induction layer precursor solution;

[0177] The induction layer described in step 1② is cobalt ferrite (CFO), and the concentration of the induction layer precursor solution is 0.2 mol / L;

[0178] The preparation method of the induction layer precursor solution described in step 1② is as follows: add cobalt nitrate and ammonium ferric sulfate to citric acid, continue stirring until completely dissolved, add 25% concentrated ammonia water dropwise to control the pH to pH = 7, and then stir at a constant temperature of 75°C to complete the reaction. When the solution is a viscous gel, stop heating, cool naturally to room temperature, and age in the dark for 24 hours to obtain an induction layer precursor solution;

[0179] The mass volume ratio of the cobalt nitrate, ammonium ferric sulfate and citric acid is 1.6g:1.8g:15mL;

[0180] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 4 layers of PZT, 3 layers of CFO, 4 layers of PZT, 3 layers of CFO and 4 layers of PZT, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate;

[0181] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each CFO layer is 0.03 μm;

[0182] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0183] 3. First, the multilayer ferroelectric film and polyethylene terephthalate (PET) are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0184] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0185] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0186] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0187] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0188] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / CFO / PZT (PZT-CFO-2);

[0189] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0190] The passivation layer described in step 5 is polyurethane;

[0191] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0192] Comparative Example 3: A method for preparing a flexible inorganic multilayer ferroelectric thin film PZT / CFO / PZT (PZT-CFO-3), which is specifically completed by the following steps:

[0193] 1. Preparation of precursor solution:

[0194] ①, using sol-gel process to prepare lead zirconate titanate (PZT) precursor solution;

[0195] The concentration of the lead zirconate titanate (PZT) precursor solution described in step 1① is 0.3 mol / L;

[0196] In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps:

[0197] Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution;

[0198] The mass volume ratio of lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL;

[0199] ②, using sol-gel process to prepare the induction layer precursor solution;

[0200] The induction layer described in step 1② is cobalt ferrite (CFO), and the concentration of the induction layer precursor solution is 0.2 mol / L;

[0201] The preparation method of the induction layer precursor solution described in step 1② is as follows: add cobalt nitrate and ammonium ferric sulfate to citric acid, continue stirring until completely dissolved, add 25% concentrated ammonia water dropwise to control the pH to pH = 7, and then stir at a constant temperature of 75°C to complete the reaction. When the solution is a viscous gel, stop heating, cool naturally to room temperature, and age in the dark for 24 hours to obtain an induction layer precursor solution;

[0202] The mass volume ratio of the cobalt nitrate, ammonium ferric sulfate and citric acid is 1.6g:1.8g:15mL;

[0203] 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, the spin coating sequence is 3 layers of PZT, 2 layers of CFO, 3 layers of PZT, 2 layers of CFO, 3 layers of PZT, 2 layers of CFO and 3 layers of PZT, and then perform rapid annealing to obtain a multilayer ferroelectric thin film on the sapphire substrate;

[0204] In step 2, the thickness of each PZT layer is 0.08 μm, and the thickness of each CFO layer is 0.03 μm;

[0205] The annealing temperature in step 2 is 700°C and the annealing time is 5 minutes;

[0206] 3. First, the multilayer ferroelectric film and polyethylene terephthalate (PET) are irradiated with ultraviolet light for 60 minutes, then a polyurethane (PU) adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate (PET) is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 60 minutes, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate;

[0207] The thickness of the polyethylene terephthalate described in step 3 is 50 μm;

[0208] Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface;

[0209] The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV;

[0210] In step 4, the XeCl excimer laser irradiates the sapphire substrate for 8 minutes;

[0211] 5. Using magnetron sputtering technology to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then covering the surface with a passivation layer to obtain a flexible inorganic multilayer ferroelectric film PZT / CFO / PZT (PZT-CFO-3);

[0212] The interdigitated electrodes in step 5 are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15 nm, and the thickness of the Au electrodes is 120 nm;

[0213] The passivation layer described in step 5 is polyurethane;

[0214] The interdigitated electrodes described in step 5 have a finger width of 100 μm and a finger spacing of 2 mm.

[0215] Figure 1 X-ray diffraction comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0216] Figure 2 X-ray diffraction comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Comparative Examples 1 to 3;

[0217] from Figures 1-2 It can be seen that the flexible inorganic multilayer ferroelectric film grows in the (100) and (200) crystal plane orientations.

[0218] Figure 3 Atomic force microscope comparison diagram of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0219] from Figure 3 The LNO induction layer can improve the surface roughness of the ferroelectric film and improve the quality of the film. Among them, the PZT-LNO-3 film has the smoothest surface.

[0220] Figure 4 A comparison diagram of hysteresis loops of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0221] from Figure 4 It can be seen that the hysteresis loop becomes thinner after the LNO induction layer is introduced, and the flexible inorganic multilayer ferroelectric film prepared by the present invention can effectively reduce energy loss. Among them, the PZT-LNO-3 film has the lowest energy loss.

[0222] Figure 5 Weibull distribution diagram of breakdown field strength of the PZT flexible ferroelectric thin film prepared in Example 1 and the flexible inorganic multilayer ferroelectric thin films prepared in Examples 2 to 4;

[0223] from Figure 5 It can be seen that the LNO induction layer can improve the quality of the film, increase the breakdown field strength of the film, and increase the service life of electronic devices.

[0224] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A flexible inorganic multilayer ferroelectric thin film, characterized in that The flexible inorganic multilayer ferroelectric film is composed of a lead zirconate titanate layer and an induction layer; the induction layer is lanthanum nickelate or cobalt ferrite.

2. A flexible inorganic multilayer ferroelectric thin film according to claim 1, characterized in that The thickness of the flexible inorganic multilayer ferroelectric film is 0.8 μm to 1.2 μm.

3. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 1, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of precursor solution: ①, using the sol-gel process to prepare the lead zirconate titanate layer precursor solution; The concentration of the lead zirconate titanate layer precursor solution described in step 1① is 0.25 mol / L to 0.4 mol / L; ②, using sol-gel process to prepare the induction layer precursor solution; When the induction layer described in step 1② is lanthanum nickelate, the concentration of the induction layer precursor solution is 0.05 mol / L to 0.15 mol / L; When the induction layer described in step 1② is cobalt ferrite, the concentration of the induction layer precursor solution is 0.15mol / L to 0.25mol / L; 2. Spin coating the lead zirconate titanate layer precursor solution and the induction layer precursor solution layer by layer on a double-sided polished sapphire substrate by spin coating, and then perform rapid annealing to obtain a multilayer ferroelectric film on the sapphire substrate; 3. First, the multilayer ferroelectric film and polyethylene terephthalate are irradiated with ultraviolet light for a period of time, then a polyurethane adhesive is spin-coated on the surface of the multilayer ferroelectric film, and then the polyurethane adhesive is irradiated with ultraviolet light, and finally the polyethylene terephthalate is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for a period of time, so that the multilayer ferroelectric film on the sapphire substrate is attached to the polyethylene terephthalate; Fourth, a XeCl excimer laser is used to irradiate the back side of the sapphire substrate to evaporate the surface between the multilayer ferroelectric film and the sapphire substrate, and the multilayer ferroelectric film is separated from the sapphire substrate and transferred to polyethylene terephthalate to obtain a PET substrate with a multilayer ferroelectric film on the surface; 5. Magnetron sputtering technology is used to grow interdigital electrodes on the surface of the multilayer ferroelectric film on the PET substrate, and then a passivation layer is covered on the surface to obtain a flexible inorganic multilayer ferroelectric film.

4. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that In step 1①, the lead zirconate titanate layer precursor solution is prepared by a sol-gel process, which is specifically completed in the following steps: Lead acetate is added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and then zirconium n-propoxide and tetrabutyl titanate are added dropwise, and the mixture is stirred at room temperature and a stirring speed of 500 rpm for 1 hour, and aged in the dark for 24 hours to obtain a lead zirconate titanate layer precursor solution; The mass volume ratio of the lead acetate, ethylene glycol methyl ether, glacial acetic acid, acetylacetone, zirconium n-propoxide and tetrabutyl titanate is 1.6 g:21 mL:5 mL:2 mL:2.7 mL:1.5 mL.

5. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that In step 1②, the induction layer precursor solution is prepared by using a sol-gel process, which is specifically completed in the following steps: When the induction layer is lanthanum nickelate, the preparation method of the induction layer precursor solution is as follows: nickel nitrate and lanthanum nitrate are added to ethylene glycol methyl ether, and then glacial acetic acid and acetylacetone are added, and the mixture is stirred at a constant temperature of 60° C. and a stirring speed of 500 rpm until the solute is dissolved, and the mixture is naturally cooled to room temperature, and aged in the dark for 24 hours to obtain an induction layer precursor solution; The mass volume ratio of the nickel nitrate, lanthanum nitrate, ethylene glycol methyl ether, glacial acetic acid, and acetylacetone is 2g:1g:13mL:2mL:1.8mL; When the induction layer is cobalt ferrite, the preparation method of the induction layer precursor solution is as follows: add cobalt nitrate and ammonium ferric sulfate to citric acid, continue stirring until completely dissolved, add 25% by mass concentrated ammonia water dropwise to control the pH to pH=7, and then stir at a constant temperature of 75°C to complete the reaction, stop heating when the solution is a viscous gel, naturally cool to room temperature, and age in the dark for 24 hours to obtain an induction layer precursor solution; The mass volume ratio of the cobalt nitrate, ammonium ferric sulfate and citric acid is 1.6g:1.8g:15mL.

6. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that The temperature of the annealing treatment in step 2 is 650° C. to 750° C., and the time of the annealing treatment is 5 min to 10 min.

7. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that The thickness of the polyethylene terephthalate described in step three is 40μm to 60μm; in step three, the multilayer ferroelectric film and the polyethylene terephthalate are first irradiated with ultraviolet light for 50min to 70min; in step three, the polyethylene terephthalate is placed on the multilayer ferroelectric film and irradiated with ultraviolet light for 50min to 70min.

8. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that The wavelength of the XeCl excimer laser described in step 4 is 308 nm, the scanning frequency is 9 Hz, and the photon energy is 4.03 eV; the time for irradiating the sapphire substrate with the XeCl excimer laser in step 4 is 5 min to 10 min.

9. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that The interdigitated electrodes described in step five are Cr electrodes and Au electrodes; the Cr electrodes are first deposited on the surface of the multilayer ferroelectric thin film on the PET substrate by magnetron sputtering technology, and then the Au electrodes are deposited; the thickness of the Cr electrodes is 15nm to 30nm, and the thickness of the Au electrodes is 120nm to 150nm.

10. The method for preparing a flexible inorganic multilayer ferroelectric thin film according to claim 3, characterized in that The passivation layer described in step 5 is polyurethane or epoxy resin; the finger width of the interdigitated electrode described in step 5 is 80 μm to 120 μm, and the finger spacing is 1 mm to 3 mm.